A Teleost CXCL10 Is Both an Immunoregulator and an Antimicrobial - Li, Huili; Sun, Yuanyuan; Sun, Li (Frontiers in Immunology, 2022)
Chemokines are a group of cytokines that play important roles in cell migration, inflammation, and immune defense. In this study, we identified a CXC chemokine, CXCL10, from Japanese flounder Paralichthys olivaceus (named PoCXCL10) and investigated its immune function. Structurally, PoCXCL10 possesses an N-terminal coil, three β-strands, and a C-terminal α-helix with cationic and amphipathic properties. PoCXCL10 expression occurred in multiple tissues and was upregulated by bacterial pathogens. Recombinant PoCXCL10 (rPoCXCL10) promoted the migration, cytokine expression, and phagocytosis of flounder peripheral blood leukocytes (PBLs). rPoCXCL10 bound to and inhibited the growth of a variety of common Gram-negative and Gram-positive fish pathogens. rPoCXCL10 killed the pathogens by causing bacterial membrane permeabilization and structure destruction. When introduced in vivo, rPoCXCL10 significantly inhibited bacterial dissemination in fish tissues. A peptide derived from the C-terminal α-helix exhibited bactericidal activity and competed with rPoCXCL10 for bacterial binding. Deletion of the α-helix affected the in vitro bactericidal activity but not the chemotaxis or in vivo antimicrobial activity of PoCXCL10. Together, these results indicate that PoCXCL10 exerts the role of both an immunoregulator and a bactericide/bacteriostatic via different structural domains. These findings provide new insights into the immune function and working mechanism of fish CXC chemokines.